Characterizations and Entropy Measures of the Exponentiated Generalized Frechet Geometric Distribution - Naz Saud; Aqsa Rafique; Muhammad Ijaz; Naila Amjad; Mahmoud El-Morshedy; Syed Habib Shah (Advances in Mathematical Physics)
Some characterizations and entropy measures of the Exponentiated Generalized Fréchet Geometric (EGFG) distribution are studied in this paper. Firstly, characterizations of the EGFG distribution based on five different approaches are discussed. The submodels for the EGFG distribution with their characterization expressions formed on the ratio of two truncated moments are also presented. Secondly, four different entropy measures are considered and expressed analytically via the incomplete gamma function. The behavior of all these entropy measures is discussed by performing a numerical study.